2021
DOI: 10.1111/jcmm.15911
|View full text |Cite
|
Sign up to set email alerts
|

CircCSNK1G3 up‐regulates miR‐181b to promote growth and metastasis via TIMP3‐mediated epithelial to mesenchymal transitions in renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) is the most common form of kidney cancer, with a high recurrence rate and metastasis capacity. Circular RNAs (circRNAs) have been suggested to act as the critical regulator in several diseases. This study is designed to investigate the role of circCSNK1G3 on RCC progression. We observed a highly expression of circCSNK1G3 in RCC tissues compared with normal tissues. The aberrantly circCSNK1G3 promoted the tumour growth and metastasis in RCC. In the subsequent mechanism investigation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
(60 reference statements)
1
11
0
Order By: Relevance
“…One study was from Germany, two studies were from The Cancer Genome Atlas (TCGA) database, and other studies were from China. Together, 20 types of circRNAs were included in the meta-analysis (circHIAT1 ( Wang et al, 2017 ; Wang et al, 2019 ), circNUP98 ( Yu et al, 2020 ), circMYLK ( Li et al, 2020a ), hsa_circ_001895 ( Chen et al, 2020a ), circ‐EGLN3 ( Lin and Cai, 2020 ), circ_001842 ( Zeng et al, 2020 ), circ_0001368 ( Chen et al, 2020b ), cRAPGEF5 ( Chen et al, 2020c ), circ-ABCB10 ( Huang et al, 2019 ), circCSNK1G3 ( Li et al, 2021 ), circAKT1 ( Zhu et al, 2020 ), circAGAP1 ( Lv et al, 2021 ), circ_101341 ( Yue et al, 2020 ), circEHD2 ( Frey et al, 2021 ), circNETO2 ( Frey et al, 2021 ), ciRS-7 ( Zhao et al, 2020 ), hsa-hsa_circ_0085576 ( Liu et al, 2020a ), circTLK1 ( Li et al, 2020b ), circPTCH1 ( Liu et al, 2020b ), and circHIPK3 ( Han et al, 2020 )). Four circRNAs (circHIAT1, circ_0001368, cRAPGEF5, and circEHD2) were downregulated, and 16 circRNAs (circMYLK, hsa_circ_001895, circ-ABCB10, circAGAP1, circEHD2, hsa_circ_0085576, circTLK1, circPTCH1, circHIPK3, circNUP98, circ‐EGLN3, circ_001842, circCSNK1G3, circAKT1, and circ_101341) were upregulated.…”
Section: Resultsmentioning
confidence: 99%
“…One study was from Germany, two studies were from The Cancer Genome Atlas (TCGA) database, and other studies were from China. Together, 20 types of circRNAs were included in the meta-analysis (circHIAT1 ( Wang et al, 2017 ; Wang et al, 2019 ), circNUP98 ( Yu et al, 2020 ), circMYLK ( Li et al, 2020a ), hsa_circ_001895 ( Chen et al, 2020a ), circ‐EGLN3 ( Lin and Cai, 2020 ), circ_001842 ( Zeng et al, 2020 ), circ_0001368 ( Chen et al, 2020b ), cRAPGEF5 ( Chen et al, 2020c ), circ-ABCB10 ( Huang et al, 2019 ), circCSNK1G3 ( Li et al, 2021 ), circAKT1 ( Zhu et al, 2020 ), circAGAP1 ( Lv et al, 2021 ), circ_101341 ( Yue et al, 2020 ), circEHD2 ( Frey et al, 2021 ), circNETO2 ( Frey et al, 2021 ), ciRS-7 ( Zhao et al, 2020 ), hsa-hsa_circ_0085576 ( Liu et al, 2020a ), circTLK1 ( Li et al, 2020b ), circPTCH1 ( Liu et al, 2020b ), and circHIPK3 ( Han et al, 2020 )). Four circRNAs (circHIAT1, circ_0001368, cRAPGEF5, and circEHD2) were downregulated, and 16 circRNAs (circMYLK, hsa_circ_001895, circ-ABCB10, circAGAP1, circEHD2, hsa_circ_0085576, circTLK1, circPTCH1, circHIPK3, circNUP98, circ‐EGLN3, circ_001842, circCSNK1G3, circAKT1, and circ_101341) were upregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Tissue inhibitor of metalloproteinases 3 (TIMP3) is a member of the TIMP family and they are the main regulators of matrix metalloproteinases 49 . Overexpression of TIMP3 was shown to inhibit the proliferation and migration of a variety of malignant tumor cells, including colorectal cancer, 49 renal cell carcinoma, 50 and liver cancer 51 . Several studies have demonstrated the targeted regulation of TIMP3 by miR‐21‐5p, miR‐221‐3p, and miR‐222‐3p 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…In the study of RCC, TGF-β1 affected the expression of miR-181b-5p to regulate the proliferation and progression of RCC (Hanusek et al, 2022). Also, miR-181b-5p was upregulated by circular RNA circCSNK1G3 to promote tumor growth and metastasis in RCC via the TIMP3-mediated epithelial-to-mesenchymal transition (EMT) process (Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%